2000
DOI: 10.1161/01.atv.20.3.751
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Secretory Group IIA Phospholipase A 2 in Relation to the Presence of Microbial Agents, Macrophage Infiltrates, and Transcripts of Proinflammatory Cytokines in Human Aortic Tissues

Abstract: Abstract-Recent seroepidemiological and immunohistochemical studies have demonstrated an association between microbial infections and atherosclerosis. However, the mechanisms underlying this association are widely unknown. In the present study, arterial specimens obtained at autopsy after sudden death were analyzed concerning (1) the presence of Chlamydia pneumoniae, cytomegalovirus, herpes simplex virus, and Helicobacter pylori; (2) the expression of secretory group IIA phospholipase A 2 (sPLA 2 -IIA) and of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 56 publications
2
21
0
2
Order By: Relevance
“…The present study additionally identified that sPLA2-II expression in gastric adenocarcinoma was associated with H. pylori infection. The results of the present study are supported by those of previous studies (17)(18)(19). These previous studies suggested that H. pylori infection may be associated with gastric cancer, and H. pylori has subsequently been identified as a World Health Organization class I carcinogen (20).…”
Section: Discussionsupporting
confidence: 91%
“…The present study additionally identified that sPLA2-II expression in gastric adenocarcinoma was associated with H. pylori infection. The results of the present study are supported by those of previous studies (17)(18)(19). These previous studies suggested that H. pylori infection may be associated with gastric cancer, and H. pylori has subsequently been identified as a World Health Organization class I carcinogen (20).…”
Section: Discussionsupporting
confidence: 91%
“…Because the arterial intima has been shown to contain snpPLA 2 , [22][23][24][25][26] and both LDL-like particles and lipid droplets 10,43 isolated from atherosclerotic lesions show signs of phospholipid hydrolysis, we suggest that the present results can be extrapolated to the actual events in the arterial intima. snpPLA 2 is found in the intimas of even early atherosclerotic lesions 24 -26 and is occasionally found in nonatherosclerotic intimas containing considerable macrophage infiltration.…”
Section: Discussionmentioning
confidence: 78%
“…26 The enzyme is able to bind to arterial PGs 21 and was found in the arterial intima in association with extracellular matrix components. 24 Most importantly, snpPLA 2 has also been found in contact with extracellular lipid droplets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations